ADDITION OF DEEP CROSS-FRICTION MASSAGE IS BETTER THAN SLOW STROKE BACK MASSAGE AFTER MCKENZIE EXERCISE TO IMPROVE FUNCTIONAL ABILITY AND WORK PRODUCTIVITY OF STONE BREAKERS WITH NON-SPECIFIC LOW BACK PAIN - Dadan Prayogo; Bernadus Sadu; Utomo Wicaksono; Fitri Gunawati (International Journal of Social Science, 2022)
Low back pain (LBP) is a condition of discomfort or acute pain in the fifth and sacral lumbar region (L5-S1). The purpose of this study was to prove the application of the intervention of adding deep cross-friction massage is better than slow stroke back massage after McKenzie exercise to improve functional ability and work productivity in stone crushers with non-specific LBP. In this study, researchers used a pretest-posttest control group design. With the number of non-specific samples of LBP in the village of Awang Bangkal Barat 12 people. The results showed that there were significant differences based on the paired-sample t-test parametric statistical test with p-value 0.00 <0.05 before and after in the treatment group and the control group based on the average ODI score and productivity. The conclusion of this study is that the addition of deep cross-friction massage is better than slow stroke back massage after McKenzie exercise to improve functional ability and work productivity of stone crushers with non-specific LBP.